2016
DOI: 10.1142/s0218301316300058
|View full text |Cite
|
Sign up to set email alerts
|

Predictions for p+Pb Collisions at sNN = 5TeV: Comparison with Data

Abstract: Predictions made in Albacete et al. [Int. J. Mod. Phys. E 22 (2013) 1330007] prior to the LHC [Formula: see text]Pb run at [Formula: see text] TeV are compared to currently available data. Some predictions shown here have been updated by including the same experimental cuts as the data. Some additional predictions are also presented, especially for quarkonia, that were provided to the experiments before the data were made public but were too late for the original publication.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 137 publications
2
40
0
Order By: Relevance
“…Our aim here is not to argue that it is indeed the dominant effect at RHIC and the LHC. Yet, a couple of recent comparisons [1,29,30] have shown that the magnitude of the gluon modification in usual nPDF fits is in reasonnable agreement with quarkonium, D and B meson data in pPb collisions at the LHC.…”
Section: Introductionmentioning
confidence: 90%
“…Our aim here is not to argue that it is indeed the dominant effect at RHIC and the LHC. Yet, a couple of recent comparisons [1,29,30] have shown that the magnitude of the gluon modification in usual nPDF fits is in reasonnable agreement with quarkonium, D and B meson data in pPb collisions at the LHC.…”
Section: Introductionmentioning
confidence: 90%
“…Thus it is possible to return to the previously released R pPb results to form a measurement-based ratio rather than employing an extrapolated p + p denominator, allowing some clarification of previous controversial results, see Ref. [4]. In addition, for the first time at the LHC, data from p + p, p+Pb and Pb+Pb collisions are now available at the same energy and thus can be compared on the same level.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the higher energy allows a somewhat broader reach in rapidity so that some processes, such as Z 0 production at LHCb, see the discussion in Ref. [4], measured near the edge of phase space, can expect higher statistics and perhaps high enough significance to be included in future global fits. Similarly, the p T reach of most processes is increased.…”
Section: Introductionmentioning
confidence: 99%
“…Methodology -The cross sections measured in pA collisions at colliders are nearly always normalized to the pp ones [7,52,53] since one is primarily interested in deviations from the free nucleon case, up to isospin effects. For DIS off a nucleus A, and thus F A 2 , the NMF R[F 2 ] is directly related to the modification R A q of the (anti)quark nPDF compared to its PDF.…”
mentioning
confidence: 99%